2021
DOI: 10.1093/mnras/stab2280
|View full text |Cite
|
Sign up to set email alerts
|

Detecting globular cluster tidal extensions with Bayesian inference – I. Analysis of ω Centauri with Gaia EDR3

Abstract: The peripheral regions of globular clusters (GCs) are extremely challenging to study due to their low surface brightness nature and the dominance of Milky Way contaminant populations along their sightlines. We have developed a probabilistic approach to this problem through utilising a mixture model in spatial and proper motion space which separately models the cluster, extra-tidal and contaminant stellar populations. We demonstrate the efficacy of our method through application to Gaia EDR3 photometry and astr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 98 publications
0
5
0
1
Order By: Relevance
“…PCB20 classify it as 'T' based on the detection of long tidal tails using Gaia DR2 by Ibata et al (2019a,b) -the socalled Fimbulthul stream. This detection is reinforced by Ibata et al (2021); the tails are also easily detectable in the region immediately surrounding the cluster, as shown by Sollima (2020) and Kuzma et al (2021). We classify this cluster as 'T'.…”
Section: A2 Classified Clustersmentioning
confidence: 86%
See 1 more Smart Citation
“…PCB20 classify it as 'T' based on the detection of long tidal tails using Gaia DR2 by Ibata et al (2019a,b) -the socalled Fimbulthul stream. This detection is reinforced by Ibata et al (2021); the tails are also easily detectable in the region immediately surrounding the cluster, as shown by Sollima (2020) and Kuzma et al (2021). We classify this cluster as 'T'.…”
Section: A2 Classified Clustersmentioning
confidence: 86%
“…As with many problems in near-field astrophysics, the availability of Gaia astrometry has led to a slew of new discoveries in this area of research, with many globular clusters now known to possess long (but generally extremely faint) tidal tails (e.g., Carballo-Bello 2019;Carballo-Bello et al 2020;Kaderali et al 2019;Sollima 2020;Ibata et al 2019bIbata et al ,a, 2021Palau & Miralda-Escudé 2021;Bonaca et al 2021;Kuzma et al 2021). However, Gaia studies are typically limited to relatively nearby clusters such that traditional groundbased wide-field imaging surveys are still useful for exploring more distant systems.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, LSST will be homogeneous and deeper. For inner halo GCs, Gaia has allowed detailed explorations of GC outskirts (e.g., de Boer et al 2019;Sollima 2020;Kuzma et al 2021). Indeed, as illustrated and quantified by Cantat-Gaudin et al (2023), the Gaia catalogs become severely incomplete in the central parts of globular clusters.…”
Section: Galactic Globular Clustersmentioning
confidence: 99%
“…Thanks to large, wellcalibrated imaging surv e ys such as Sloan Digital Sky Survey (SDSS; Ahn et al 2012 ) and Pan-STARRS1 (PS1; Chambers et al 2016 ), as well as the more recent astrometric Gaia space mission (Gaia Collaboration et al 2018 ), tidal features have been found around a few tens of GCs in the MW halo (e.g. Sollima 2020 ; Kuzma et al, in preparation), ranging from the massive inner halo NGC 5139 (Ibata et al 2019 ;Kuzma, Ferguson & Pe ˜ narrubia 2021 ) to the lowmass outer halo Palomar 1 (Niederste-Ostholt et al 2010 ). The most emphatic display of tidal features in the MW, ho we ver, belongs to Palomar 5 (Pal 5; Odenkirchen et al 2001Odenkirchen et al , 2003.…”
Section: Introductionmentioning
confidence: 99%